Differences in cerebral cortical anatomy of left- and right-handers - Guadalupe, Tulio; Willems, Roel M.; Zwiers, Marcel P.; Arias Vasquez, Alejandro; Hoogman, Martine; Hagoort, Peter; Fernández, Guillén; Buitelaar, Jan; Franke, Barbara; Fisher, Simon E.; Francks, Clyde (Frontiers in Psychology, 2014)
The left and right sides of the human brain are specialized for different kinds of information processing, and much of our cognition is lateralized to an extent towards one side or the other. Handedness is a reflection of nervous system lateralization. Roughly ten percent of people are mixed- or left-handed, and they show an elevated rate of reductions or reversals of some cerebral functional asymmetries compared to right-handers. Brain anatomical correlates of left-handedness have also been suggested. However, the relationships of left-handedness to brain structure and function remain far from clear. We carried out a comprehensive analysis of cortical surface area differences between 106 left-handed subjects and 1960 right-handed subjects, measured using an automated method of regional parcellation (FreeSurfer, Destrieux atlas). This is the largest study sample that has so far been used in relation to this issue. No individual cortical region showed an association with left-handedness that survived statistical correction for multiple testing, although there was a nominally significant association with the surface area of a previously implicated region: the left precentral sulcus. Identifying brain structural correlates of handedness may prove useful for genetic studies of cerebral asymmetries, as well as providing new avenues for the study of relations between handedness, cerebral lateralization and cognition.